2021
DOI: 10.3389/fimmu.2021.587440
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Differential Methylation Integration Analysis Identified Important Differential Methylation Annotation Genes and Functional Epigenetic Modules Related to Vitiligo

Abstract: Vitiligo is an pigmentation disorder caused by a variety of pathogenic factors; its main pathophysiological conditions include oxidative stress, immune activation, and genetic background. Additionally, DNA methylation is often associated with the pathogenesis of vitiligo; however, the underlying mechanism remains unknown. In the present study, we used the Human Methylation 850K BeadChip platform to detect DNA methylation changes in the vitiligo melanocytes. We then integrated the results with the transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…It was a practicality for most biological studies (Fortino et al, 2020;Shen et al, 2020;Unger et al, 2020). Among these important transcriptomic features, several top-ranked variables were closely related to the melanogenesis and immune characteristics, which was the main phenotypes of vitiligo (Picardo et al, 2015;Niu and Aisa, 2017;Pu et al, 2021;Zhang et al, 2021). Moreover, we constructed a more comprehensive VitNet and obtained 160 articulation proteins by the GAPR method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was a practicality for most biological studies (Fortino et al, 2020;Shen et al, 2020;Unger et al, 2020). Among these important transcriptomic features, several top-ranked variables were closely related to the melanogenesis and immune characteristics, which was the main phenotypes of vitiligo (Picardo et al, 2015;Niu and Aisa, 2017;Pu et al, 2021;Zhang et al, 2021). Moreover, we constructed a more comprehensive VitNet and obtained 160 articulation proteins by the GAPR method.…”
Section: Discussionmentioning
confidence: 99%
“…Among these articulation proteins, previous study had reported that Imatinib (ABL1 inhibitor) induced repigmentation of vitiligo lesions ( Han et al, 2008 ). A recent study also found that PBK, CDK1 and TXN were considered as potential therapeutic targets by transcriptome and methylation analysis ( Pu et al, 2021 ). However, whether these targets were related to melanogenesis had not been proved.…”
Section: Discussionmentioning
confidence: 99%
“…The Kyoto Encyclopedia of Genes and Genomes (KEGG) ( https://www.kegg.jp/ ) ( Kanehisa et al, 2017 ) is a database that provides gene and genome functional significance at the molecular and pathway levels. The DOSE, ClusterProfiler, Org.Hs.eg.db, and Enrichplot packages in R ( Yu et al, 2012 ; Yu et al, 2015 ; Pu et al, 2021 ) were used for the GO and KEGG pathway enrichment analyses of DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression quantification was performed using RSEM (17) to obtain the fragment per kilo exon per million reads (FPKM) of each gene. DEGs were analyzed using DEseq2, and the clusterProfiler of the R software package was used to perform gene pathway enrichment analysis with a threshold of p < 0.05 (18)(19)(20). The enrichment analysis mapping was performed using a p-value.…”
Section: Rna Sequencing Datamentioning
confidence: 99%